Stratigraphy of the Chubut Group (Cretaceous, Golfo San Jorge Basin, Argentina): impacts of allogenic controls on the alluvial macro-architecture (Latin American Journal of Sedimentology and Basin Analysis, 2025)
The Chubut Group (Cretaceous, Golfo San Jorge Basin) is a continental succession up to 6,000 meters thick, preserved in an endorheic basin. Its basal depositional system includes the fluvial Matasiete Formation and the lacustrine Pozo D-129 Formation, the main source rock for the hydrocarbons of the basin. The Matasiete Formation (Aptian) represents a high-accommodation,  exotic fluvial system with headwaters in the present-day Cañadón Asfalto Basin (CAB), referred to as the Los Adobes Formation. Sediment was transported  southward to a saline-alkaline lake (Pozo D-129 Formation) through N-S sedimentary corridors in an extensional setting. The overlying depositional system is integrated by the Castillo and Mina del Carmen formations (Albian-Cenomanian?), and it consists of reworked volcaniclastic particles in drainage catchments within a W-E elongated extensional basin, disconnected from the CAB. The subsequent depositional system includes the Bajo Barreal Formation (Cenomanian-Coniacian?), containing the main hydrocarbon reservoirs. It shows varied stacking density in hundreds of meters thick cycles, linked to climatic cycles. Low net-to-gross fluvial stratigraphy featuring small-scale channel belts and paleosols indicates a temperate, subhumid/humid climate with seasonal rainfall. High net-to-gross fluvial stratigraphy records larger-scale channel belts interbedded with paleosols developed in a warmer, humid climate with perennial rainfall. The uppermost depositional system includes the paleosol-rich Laguna Palacios Formation at basin margins, with maximum thicknesses along syncline axes, and the red-colored, anastomosing fluvial systems of the Maastrichtian Colhué Huapi Formation that fill incised valleys. Both units are equivalent to the upper strata of Meseta Espinosa and El Trébol formations in the subsurface, showing degradational features marking the onset of surface uplift in the San Bernardo Fold Belt.
Keywords: endorheic basin; Cretaceous fluvial systems; alluvial architecture; allogenic controls; Patagonia